Predictors of essential health and nutrition service delivery in Bihar, India: Results from household and frontline worker surveys - Kosec, Katrina; Avula, Rasmi; Holtemeyer, Brian; Tyagi, Parul; Hausladen, Stephanie; Menon, Purnima (Johns Hopkins University Press, 2015)
In Bihar, India, coverage of essential health and nutrition interventions is low. These interventions are provided by 2 national programs–the Integrated Child Development Services (ICDS) and Health/National Rural Health Mission (NRHM)–through Anganwadi workers (AWWs) and Accredited Social Health Activists (ASHAs), respectively. Little is known, however, about factors that predict effective service delivery by these frontline workers (FLWs) or receipt of services by households. This study examined the predictors of use of 4 services: (1) immunization information and services, (2) food supplements, (3) pregnancy care information, and (4) general nutrition information.Data are from a 2012 cross-sectional survey of 6,002 households in 400 randomly selected villages in 1 district of Bihar state, as well as an integrated survey of 377 AWWs and 382 ASHAs from the same villages. For each of the 4 service delivery outcomes, logistic regression models were specified using a combination of variables hypothesized to be supply- and demand-side drivers of service utilization.About 35% of households reported receiving any of the 4 services. Monetary immunization incentives for AWWs (OR = 1.55, CI = 1.02-2.36) and above-median household head education (OR = 1.39, CI = 1.05-1.82) were statistically significant predictors of household receipt of immunization services. Higher household socioeconomic status was associated with significantly lower odds of receiving food supplements (OR = 0.87, CI = 0.79-0.96). ASHAs receiving incentives for institutional delivery (OR = 1.52, CI = 0.99-2.33) was marginally associated with higher odds of receiving pregnancy care information, and ASHAs who maintained records of pregnant women was significantly associated with households receiving such information (OR = 2.25, CI = 1.07-4.74). AWWs receiving immunization incentives was associated with significantly higher odds of households receiving general nutrition information (OR = 1.92, CI = 1.08-3.41), suggesting a large spillover effect of incentives from product- to information-oriented services.Product-oriented incentives affect delivery of both product- and information-oriented services, although household factors are also important. In India, existing government programs can mitigate supply- and demand-side constraints to receiving essential interventions by optimizing existing incentives for FLWs in national programs, helping FLWs better organize their work, and raising awareness among groups who are less likely to access services.